Perancangan Sistem Informasi Manajemen Karyawan di PT. Aqualuxe Perkasa Abadi (Kohesi: Jurnal Sains dan Teknologi, 2025)
The development of the modern industry demands efficiency in human resource management, especially in the recording of employee data, overtime, and payroll. PT. Aqualuxe Perkasa Abadi is still using a manual method that results in a lack of data integration and delays in information. This research aims to design and implement a web-based employee management information system using the Waterfall method. The development process includes needs analysis, interface design, implementation using PHP with the Bootstrap Framework and MySQL, and testing using the blackbox method. The results obtained are an integrated system that can enhance HRD administration efficiency, minimize recording errors, and provide real-time access to personnel data. This system is expected to support the internal work processes of the company more quickly, accurately, and precisely